PERCEPTION, MISCONCEPTIONS AND SATISFACTION REGARDING CHHAYA (NON-HORMONAL WEEKLY CENTCHROMAN PILL) AMONG WOMEN WITHIN REPRODUCTIVE AGE GROUP ATTENDING GYNECOLOGICAL OUT PATIENT DEPARTMENT IN A SELECTED HOSPITAL, KOLKATA - Roy, Ishita; Mazumder, Manika; Ghosh, Rakhi (International Journal of Research -GRANTHAALAYAH, 2024)
Population growth is a serious threat to the international community and a major obstacle for nation’s social and economic development, moreover it is one of the biggest problems developing country like India is facing at the moment and to satisfy the need of contraceptive as well as to fulfill the undertaking of the 2030 Agenda GOI has introduced ‘Centchroman’, non-hormonal or non-steroid based weekly pill which is relatively safer and better choice as contraceptive for the reproductive age women even for breastfeeding women as it has no side-effects like other steroidal contraceptives. Aim: This study aims to assess the Perception, Misconceptions and Satisfaction regarding CHHAYA (Non-hormonal weekly Centchroman Pill) among women within the reproductive age group attending the Gynecological Out Patient Department in a selected hospital, Kolkata. Methods: An exploratory survey research was carried out with 115 reproductive age group women using CHHAYA attending the Gynecological Out Patient Department in a selected hospital, Kolkata. The Total enumerative sampling technique was employed to select as subjects and the Data was collected by using self-developed, validated demographic proforma, perception assessment scale, misconception rating scale, satisfaction assessment tool through interviewing technique. Results: The findings revealed that of all these women, 51.30% had positive perception, 60% had misconceptions and 55.65% respondents were satisfied with CHHAYA. Statistically a significant relationship was found between the perception and the satisfaction of the women regarding CHHAYA (‘ρ’=0.61, ‘t’ =8.18, p= 0.0008). Statistically significant association found between level of perception and partner’s approval (ꭓ2 = 5.94, p =0.01), duration of use (ꭓ2 = 7.65, p =0.005). It has also been outlined that there was statistically significant association between level of misconception and the religion (ꭓ2 = 6.94, p =0.008), education level of the women (ꭓ2 = 6.16, p =0.01). It also depicted that there was statistically significant association between level of satisfaction and the type of family (ꭓ2 = 8.33, p =0.003), partners approval (ꭓ2 = 4.64, p =0.03), duration of use (ꭓ2 = 8.93, p =0.002). Conclusion: In spite of the fact that CHHAYA is an effective, inexpensive, easily accessible, lack of stringent schedule, safe in terms of side-effects like other OCPs, non-interference with sexual drive, reversible contraceptive method for women who opt for family planning it is mostly underutilized among contraceptives as there is negative perception, strong misconceptions, lack of satisfaction. As it is till now underuse due to insufficient information about it among the women, so collaborative efforts of proper counselling and follow up can be made by the health care providers reducing the misconceptions, discontinuation rates and to sustain compliance to CHHAYA.